A singularidade do sacrifício de Cristo: uma abordagem ético-teológica a partir da obra de René Girard. - Silva, Genilson Sousa da (2023)
This research aimed to deepen, in the light of René Girard's mimetic theory, the meaning of Christ's sacrifice as overcoming the sacrificial logic, seeking to problematize the mission of Christianity and its ethical role in contemporary times. Specifically, we sought to verify the logic of mimetic desire from its cultural development, from the perspective of conflicting relationships to the construction of the scapegoat. For this, we made an allusion to the concept of sacrificial victim, taking into account the accounts of the Passion, from the prophetic scriptures of the Old Testament, as well as the revealing differentiation by intelligence of the donor victim in the New Testament; in view of sacrifice in mythical cultures, that is, through mythological narratives, encompassed by Greek culture and other cultures. In addition, a reflective path was built that interconnects the presence of Christianity in the current scenario, which is marked by violence and a culture of death, as well as the ethical role of Christians in the preservation of life. In this way, it was noticed that, with the light coming from anthropology, theology rediscovered the ethical role of Christianity in today's world. The resumption of this awareness occurred, above all, by deepening the mimetic desire and its consequences, which have several references, especially in human relationships. With this foundation, Christianity presents itself as a model of conflict resolution, which since the Jewish tradition was committed to resolving them through solidary love in defense of the victims, not through violence itself. The uniqueness of Christ's sacrifice points out, through Jesus' way of life, mechanisms that direct towards models of relationships focused on ethics, both in terms of care in defense of the victims, as well as human liberation from mimetic cycles. Girard's mimetic theory, in line with anthropological data, enables the understanding of the Christian vocation in our days and, at the same time, enhances and revitalizes the Christian's action in the world - as witnesses of fraternal and healthy relationships, which show in the being human the ability to experience the solidary wisdom that comes from Jesus and through resilient survivors. With this, this work brings as a result, the awareness of Christians, of the present time, in view of the intelligence of the victim, that is, the Trinitarian relationship that moved the life of Jesus, and that gives meaning to the life of each Christian, as well as , the understanding of Christ's loving logic in giving himself consciously and freely, going against the culture of the conflicting mechanism in human relationships.